Converse flexoelectricity yields large piezoresponse force microscopy signals in non-piezoelectric materials - Abdollahi, Amir; Domingo, Neus; Arias, Irene; Catalan, Gustau (Nature communications, 2019)
Converse flexoelectricity is a mechanical stress induced by an electric polarization gradient. It can appear in any material, irrespective of symmetry, whenever there is an inhomogeneous electric field distribution. This situation invariably happens in piezoresponse force microscopy (PFM), which is a technique whereby a voltage is delivered to the tip of an atomic force microscope in order to stimulate and probe piezoelectricity at the nanoscale. While PFM is the premier technique for studying ferroelectricity and piezoelectricity at the nanoscale, here we show, theoretically and experimentally, that large effective piezoelectric coefficients can be measured in non-piezoelectric dielectrics due to converse flexoelectricity. Piezoresponse force microscopy (PFM) is widely used to study piezoelectric properties of materials. Here, the authors not only show that PFM measurements will yield a signal even in non-piezoelectric materials via induced flexoelectricity, but also introduce a protocol to distinguish these from real signals.